Pengembangan Topik Pembelajaran SQL – DDL Menggunakan DBMS MYSQL Pada Platform Intelligent Computer-Assisted Programming Learning Platform (ICLOP) - Ali Rahman Wibisana, Hafid; Puspitasari, Dwi; Fahrur Rozi, Imam (Politeknik Negeri Malang, 2023)
Learning about databases at Polinema campus still relies on several lecturers within the database courses. However, due to limited time, the lecturers have constraints in conducting database course lessons, typically once a week for 3 credit hours. Additionally, lecturers have commitments outside the campus, affecting the efficiency of their assessments for students. Therefore, there is a need for a SQL – DDL learning system using MySQL on the iClop platform. The designed and implemented system utilizes PHP, MySQL, MyTAP, HTML, CSS, JavaScript, Bootstrap, and others. The system has been tested by various users, and the results show that each user can engage in SQL - DDL learning and exercises. The system also provides users with grades based on their performance.